2021
DOI: 10.1038/s41598-021-83691-2
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady MHD natural convection flow of Casson fluid incorporating thermal radiative flux and heat injection/suction mechanism under variable wall conditions

Abstract: Unsteady magnetohydrodynamic flow of Casson fluid over an infinite vertical plate is examined under ramped temperature and velocity conditions at the wall. Thermal radiation flux and heat injection/suction terms are also incorporated in the energy equation. The electrically conducting fluid is flowing through a porous material and these phenomena are governed by partial differential equations. After employing some adequate dimensionless variables, the solutions are evaluated by dint of Laplace transform. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 47 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…where Bo denotes magnetic field strength, u represents velocity component along x direction, v is the velocity component along y direction, ρ∞ is the density of the fluid, µ∞ is the fluid dynamic viscosity, κ is the fluid thermal conductivity, ν∞ is the kinematic viscosity, σ denotes fluid electrical conductivity, cp is the fluid specific heat at constant pressure, uw is velocity with which the plate is moving, K * c is the rate of chemical reaction and D signifies mass diffusivity. qr represents radiative heat flux which based on Rosseland approximation [21] is expressed as…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…where Bo denotes magnetic field strength, u represents velocity component along x direction, v is the velocity component along y direction, ρ∞ is the density of the fluid, µ∞ is the fluid dynamic viscosity, κ is the fluid thermal conductivity, ν∞ is the kinematic viscosity, σ denotes fluid electrical conductivity, cp is the fluid specific heat at constant pressure, uw is velocity with which the plate is moving, K * c is the rate of chemical reaction and D signifies mass diffusivity. qr represents radiative heat flux which based on Rosseland approximation [21] is expressed as…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Recently, Khan et al [20] investigated heat generation and natural convection effects on incompressible nanofluids along a sphere in the presence of Brownian motion and thermophoresis. Anwar et al [21] investigated MHD free convective flow of an optically thick Casson fluid in the presence of heat generation. Oyelami et al [22] presented numerical solutions of chemical reaction parameter and radiation parameter effects on natural convection MHD flow on non-Newtonian fluid between porous plates.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25] Recently, unsteady incompressible magnetohydrodynamics (MHD) flow of Casson fluid, subjected to ramped velocity and ramped temperature conditions at a vertical wall placed in the porous medium is studied in. 26 The concept of Fractional differential equations is considered as an alternative tool to model nonlinear differential equations. The history of fractional calculus is mainly based on the article by, Miller and Ross 27 and recent review articles.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Sohail et al [20] discussed the momentum, concentration, and thermal diffusion in the surface layer magneto-flow of the Casson material in an elongated plate. Other studies related to the Casson material can be found in ( [21][22][23]).…”
Section: Introductionmentioning
confidence: 99%